Vibrancy of Public Spaces Inclusivity and Participation Amidst the Challenges in Transformative Process in the City of Cagayan De Oro, Philippines - Satur, Luzile
This study examines the dynamics which lead to revitalization of everyday life in the public spaces of Cagayan de Oro, a medium-sized urban center in Northern Mindanao, the Philippines. By employing the oriental philosophies together with western thoughts such as Henri Lefebvre, Alain Touraine and Jürgen Habermas, this study elucidates that the core of perceived, lived and conceived spaces is ‘the Subject.’ Once the Subject utilizes the public sphere to instill social action, social space is ultimately produced. Hawkers, grassroots environmental activists, street readers and artists are the social Subjects who partake in the vibrancy of public spaces. The social Subjects utilize public spaces as venues of social transformation. Thus, this study argues that the social Subjects’ role in democratic process lead to inclusivity of the marginalized sector in the public spaces of the city.